Diseño de una ruta turística de los lugares sagrados de la parroquia de Salasaka, cantón Pelileo, provincia de Tungurahua. - Masaquiza Chicaiza, Tannia Maribel (2024)
The present research proposes to design the tourist route of the sacred places of the Salasaka Kichwa people, to strengthen tourism in the Pelileo canton, province of Tungurahua. Therefore, the first objective was carried out through the qualitative method that allowed us to analyze the situational diagnosis of the Salasaka parish through the bibliographic review of sources such as the PDOT and thesis documents related to the topic, in addition, as part of the analysis, a survey was carried out to know the profile of the tourist who turned out to be a person, mostly male, between 25 and 45 years old, with third level studies, his national origin is from Quito and internationally from England, and The main reason for the trip is tourism, thus an interview was also applied to the key actors to learn about the existence of tourist routes in the Salasaka parish, the parish has 17 communities with more than 5,886 inhabitants and two recognized tourist places, which are the Salasaka craft market and the Wasalata viewpoint. For the second objective, the exploratory method was used through which the Hierarchization methodology of tourist attractions of the MINTUR was applied with the use of the cards. As a result, a total of five attractions were obtained which were part of the route and they are: Chakana Pamba, Kinlli Urko, Palama, Punta Rumi, Phukiu yaku jhuakcha pata. In addition, the INPC methodology was applied with the ethnographic method through which the inventory of Intangible Heritage of the ancestral elements that are reason, intuition, heart and perception could be developed. To finish with the third objective, the descriptive method was used through which the design of the route was carried out with the use of the SENA methodology where phase one of the route structure was applied, the classification of attractions was carried out, phase two determination and selection of the services to be included in the route, in this the services to be applied in the route were selected, phase three determination of costs and operating expenses, the route budget was made, and phase four determination of prices and net operating benefits. Designed the package budget of the elaborate route, resulting in the route that bears the name of SUMAK ÑAN PURINA, and has five sacred attractions that surround the most important points that, according to the Yachak/Amauta of the Salasaka parish, can be found in them. Perform cleansing and rituals on interested people since at these points there is the necessary energy that they use to carry them out. In addition, two packages were designed, a full day and a two-day package, each one has an itinerary, budget and script of the tour to be taken.